Pertumbnhan Ikan Tambra (Tor tambroides) dan Kancera (Tor soro) Pada Proses Domestikasi dengan Jenis Pakan yang Berbeda - Haryono, Haryono; Subagja, Jojo (JURNAL BIOLOGI INDONESIA, 2007)
ABSTRACTThe Growth of Tarnbra fish (Tor tambroides) and Kancera fish (Tor soro) inDomestication Process with Different Fed. The experiment was conducted toevaluate the growth of two mahseer (tambra and kancera) from Muller Mountainareas in Central Kalimantan which were different fed in aquarium i.e: A. Frozenworm, B. Fish feed, and C. shrimp feed. The experiment follows Randomized CompleteDesign Methods. The replication of treatment is three times, each aquarium filled with1 individual as treatment and replication. They were fed daily for 100 days andmeasured each 20 days. The results showed shrimp feed gave growth fastest (0.460gldays), and the lowest is 0.170 gldays; the growth oftambra fish faster than kancerafish. The water quality of aquarium is suitable for growing these fish.Kata kunci: Growth, Tambra fish (Tor tambroides), Kancera fish (Tor soro), Fed